Electrochemical protease biosensor based on enhanced AC voltammetry using carbon nanofiber nanoelectrode arrays - Swisher, Luxi Zhang; Syed, Lateef U.; Prior, Allan M.; Madiyar, Foram R.; Carlson, Kyle R.; Nguyen, Thu A.; Hua, Duy H.; Li, Jun (My University, 2013)
We report an electrochemical method for measuring the activity of proteases using nanoelectrode arrays (NEAs) fabricated with vertically aligned carbon nanofibers (VACNFs). The VACNFs of ~150 nm in diameter and 3 to 5 μm in length were grown on conductive substrates and encapsulated in SiO[subscript 2] matrix. After polishing and plasma etching, controlled VACNF tips are exposed to form an embedded VACNF NEA. Two types of tetrapeptides specific to cancer-mediated proteases legumain and cathepsin B are covalently attached to the exposed VACNF tip, with a ferrocene (Fc) moiety linked at the distal end. The redox signal of Fc can be measured with AC voltammetry (ACV) at ~1 kHz frequency on VACNF NEAs, showing distinct properties from macroscopic glassy carbon electrodes due to VACNF’s unique interior structure. The enhanced ACV properties enable the kinetic measurements of proteolytic cleavage of the surface-attached tetrapeptides by proteases, further validated with a fluorescence assay. The data can be analyzed with a heterogeneous Michaelis-Menten model, giving “specificity constant” k[subscript cat]/K[subscript m] as (4.3 ± 0.8) x 10[superscript 4] Mˉ¹sˉ¹ for cathepsin B and (1.13 ± 0.38) x 10[superscript 4] Mˉ¹sˉ¹ for legumain. This method could be developed as portable multiplex electronic techniques for rapid cancer diagnosis and treatment monitoring.
Keywords: Nanoelectrode array; Legumain; Cathepsin B; Enzymatic kinetics; AC voltammetry